Pomegranate seed hydroalcoholic extract improves memory deficits in ovariectomized rats with permanent cerebral hypoperfusion /ischemia - Alireza Sarkaki; Yaghoob Farbood; Shieda Hashemi; Maryam Rafiei Rad (Mashhad University of Medical Sciences, 2014)
Objective: Estrogen deficit following menopause results in cognitive behaviors impairment. Severity of these impairments in menopause women suffer with cerebral hypo perfusion/ischemia (HI) cause the brain damage and neuronal death. This study aimed to evaluate the effects of pomegranate seed extract (PGSE) on avoidance memories after permanent bilateral common carotid arteries occlusion (2CCAO) in ovariectomized (OVX) rats. Materials and Methods: Adult female Wistar rats were divided randomly into eight groups with 8 rats in each group: 1) Sham-operated for ovaries and 2CCAO (ShO); 2) OVX and sham operated for ischemia (OShI); 3-7) OVX with 2CCAO (OI) received PGSE (100, 200, 400 and 800 mg/2ml/kg or normal saline, orally) for 14 days (OI+E100, 200, 400, 800 or OI+Veh); 8) OShI received most effective dose of PGSE (200 and 400 mg/kg for passive and active avoidance memories respectively). Active and passive avoidance tasks were measured in Y-maze and two-way shuttle box respectively. Data were analyzed with one-way and RM-ANOVA followed by HSD post-hoc test. Results: Sensorimotor impaired in OShI+Veh and OI+Veh (P